Counseling Muslim Couples From a Bowen Family Systems Perspective. (April 2014) - Sauerheber, Jill Duba; Nims, Donald; Carter, David J.
To date, there is very little literature to guide mental health practitioners working with Muslim couples and families in the United States. Cultural differences may be expected to limit the relevance of some approaches; but Bowen theory seems to have particular relevance for Muslim couples. Counselors practicing Bowen Family Systems theory serve as consultants engaging the couple in the processing and understanding of current patterns of dysfunctional behavior. This article reviews basic tenets of Bowen theory, summarizes some common experiences of Muslim couples living in America, and suggests ways in which Bowen theory can be applied in a way that is respectful to the unique values, history, and expectations of Muslim couples. A case study is provided.